2022
DOI: 10.1002/sia.7149
|View full text |Cite
|
Sign up to set email alerts
|

The role of organic compounds in artificial saliva for corrosion studies: Evidence from X‐ray photoelectron spectroscopy

Abstract: Several formulations of artificial saliva have been used for corrosion studies. The present work focuses on the effect of different saliva formulations on the composition of the surface film formed on CuZn37 brass alloy by X-ray photoelectron spectroscopy (XPS), in order to clarify the corrosion mechanism of historical brass wind instruments when used. Three different saliva solutions, Darvell (D), Carter-Brugirard (C-B) and SALMO, were selected. They differ for the content of the organic compounds. The XPS re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…It was demonstrated that when citrate was present, the thickness of the passive layer decreased, and the chromium and molybdenum oxide content in the passive film was higher than in the purely inorganic Hanks’ solution . In the framework of a project devoted to investigate the corrosion of brass wind instruments, the corrosion behavior of brass in different solutions simulating artificial saliva was studied, and it was shown that the presence of organic ligands in the formulation affects the corrosion rate, thickness, and composition of the surface film formed upon exposure of the brass to the solutions. Citrate ions favored zinc dissolution, limiting the precipitation of the protective zinc phosphate layer. , In this paper, the effect of three artificial saliva formulations differing in the content of organic compounds on the corrosion resistance of the Ni-free DIN 1.4456 stainless steel is investigated.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…It was demonstrated that when citrate was present, the thickness of the passive layer decreased, and the chromium and molybdenum oxide content in the passive film was higher than in the purely inorganic Hanks’ solution . In the framework of a project devoted to investigate the corrosion of brass wind instruments, the corrosion behavior of brass in different solutions simulating artificial saliva was studied, and it was shown that the presence of organic ligands in the formulation affects the corrosion rate, thickness, and composition of the surface film formed upon exposure of the brass to the solutions. Citrate ions favored zinc dissolution, limiting the precipitation of the protective zinc phosphate layer. , In this paper, the effect of three artificial saliva formulations differing in the content of organic compounds on the corrosion resistance of the Ni-free DIN 1.4456 stainless steel is investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The three formulations here adopted were as follows: Darvell (D), 17 Carter-Brugirard (C-B), 18 and SALMO, 19 which were previously used also for investigations on brass corrosion. 11,12 The role of organic compounds that may act as ligands is evaluated here for the first time in order to shed light on the corrosion resistance of the steel following contact with solutions simulating more closely the real conditions where the brackets are in contact with biological fluids.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Morphological characterization was carried out by optical microscopy and the films grown on the sample surfaces were characterized by X-ray photoelectron spectroscopy (XPS). [17] 2 | MATERIALS AND METHODS…”
Section: Introductionmentioning
confidence: 99%